Analisis Koefisien Kekasaran Sungai Di Sungai Sario Dengan Persamaan Manning - Adenancy A. Montjai; Johan A. Rombang; Josephus I. Kalangi (Universitas Sam Ratulangi, 2015)
ABSTRACT Analysis of River Roughness Coefficient in Sario River with Manning Equation Sario river is the main river of Sario Watershed. Due to rapidly increasing population, protected area alongside river border had become settlement. This causes a decrease of river channel capacity so that flood could happen as a case in January 2014. Manning equation is the formula frequently used to calculate the flow capacity of open channel. The purpose of this research is to determine roughness coefficient of Sario River by using Manning equation. This research was done in three months starting from January 2015 to March 2015. Observed and measured variables were river width, top width, bottom width, water depth, river channel depth, river pseudosection profile, flow velocity, gradient of bottom channel, and channel description. Method applied was survey method and the determination of measurement and observation points was done with certain consideration (purposive sampling). The averages of calculated roughness coefficients of Sario River are 0,049 for upstream, 0,050 for middlestream, and 0,060 for downsrtream. The average of Sario River roughness coefficient is 0,048. Garbage and water countaining dispersed particles caused roughness coefficient greater than secondary data for natural channel. Keywords : River Roughness, Manning equation, Sario River